Uterine fibroids — Causes, impact, treatment, and lens to the African perspective - Sefah, Narvella; Ndebele, Sithembinkosi; Prince, Lillian; Korasare, Elizabeth; Agbleke, Michael; Nkansah, Annabella; Thompson, Humphrey; Al-Hendy, Ayman; Agbleke, Andrews Akwasi (Frontiers in Pharmacology, 2023)
Leiomyomas, or uterine fibroids as they are commonly known, are mostly seen in women of reproductive age. However, they can go undetected in most women, and approximately 25% of women show clinical symptoms. Although fibroids are a global burden impacting 80% of premenopausal women, they are more prevalent among Black women than among women of other races. Based on clinical diagnosis, the estimated cumulative incidence of fibroids in women ≤50 years old is significantly higher for black (>80%) versus white women (∼70%). The cause of leiomyomas is not clearly known, but studies have shown evidence of factors that drive the development or exacerbation of the disease. Evidence has linked risk factors such as lifestyle, age, environment, family history of uterine fibroids, and vitamin D deficiencies to an increased risk of uterine fibroids, which impact women of African descent at higher rates. Treatments may be invasive, such as hysterectomy and myomectomy, or noninvasive, such as hormonal or nonhormonal therapies. These treatments are costly and tend to burden women who have the disease. Sub-Saharan Africa (SSA) is known to have the largest population of black women, yet the majority of uterine fibroid studies do not include populations from the continent. Furthermore, the prevalence of the disease on the continent is not well determined. To effectively treat the disease, its drivers need to be understood, especially with regard to racial preferences. This paper aims to review the existing literature and build a case for conducting future research on African women.